2019
DOI: 10.3390/ijms20092240
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Reconstructed Full Thickness Skin Model, T-Skin™, and its Application for Investigations of Anti-Aging Compounds

Abstract: Background: We have characterized a new reconstructed full-thickness skin model, T-Skin™, compared to normal human skin (NHS) and evaluated its use in testing anti-aging compounds. Methods: The structure and layer-specific markers were compared with NHS using histological and immunohistological staining. In anti-aging experiments, T-SkinTM was exposed to retinol (10 µM) or vitamin C (200 µM) for 5 days, followed by immunohistological staining evaluation. Results: T-Skin™ exhibits a well stratified, differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 57 publications
4
30
0
Order By: Relevance
“…Vitamin C is a powerful free radical scavenger observed in high concentrations of the epidermis and dermis, protecting skin against ROS‐induced oxidative damage 9,14 . However, UV‐induced damage may reduce the antioxidant defense system in skin, including the levels of vitamin C 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin C is a powerful free radical scavenger observed in high concentrations of the epidermis and dermis, protecting skin against ROS‐induced oxidative damage 9,14 . However, UV‐induced damage may reduce the antioxidant defense system in skin, including the levels of vitamin C 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was showed that vitamin C encapsulated into liposomes enhances the deposition of the collagen type I in mouse embryo fibroblasts after 48 hours 38 . In artificial human skin, the administration of vitamin C promotes the synthesis of the collagen types VII and IV, laminin V, and procollagen type I in the dermis after 5 days 14 . In our study, formulation 1 diluted at 50% reduced the gene expression of ECM components (Col1a1, Fbn1, and Eln), protein and gene levels of housekeeping markers (actin, Rlp10, and GAPDH), and cell proliferation (lower PCNA levels) in the human skin ex vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years tissue engineered HSEs have been established as valid models for in-vitro cosmetic and pharmaceutical testing, as well as for the investigation of skin biology mechanisms behind the generation of the epidermis, skin barrier repair/wound healing, skin pathologies and absorption testing (Schäfer-Korting, Mahmoud, et al, 2008;Xie et al, 2010;Ali et al, 2015;De Vuyst et al, 2017;Lewis et al, 2018;Bataillon et al, 2019).…”
Section: D Skin Models and Skin Absorptionmentioning
confidence: 99%
“…Chapter 7: Conclusion and future work Conclusion 3D in-vitro tissue models of human skin represent a valid alternative to monolayer 2D cell culture, ex-vivo human and animal skin models, and, at the present time, their application finds a place in many skin research fields (Schäfer-Korting, Mahmoud, et al, 2008;Xie et al, 2010;Ali et al, 2015;De Vuyst et al, 2017;Lewis et al, 2018;Bataillon et al, 2019). 3D in-vitro skin models offer several advantages; they have a higher resemblance to the in-vivo human skin microenvironment compared to monolayer 2D cell culture, they guarantee a higher quality of preservation compared to ex-vivo skin, as they are still living systems they are easy to obtain without requiring an individual ethical licence, and they represent a valid replacement to animal testing in line with the principle of the UK organisation 3Rs (Replacement, Reduction and Refinement).…”
mentioning
confidence: 99%